2019
DOI: 10.1111/exd.13874
|View full text |Cite
|
Sign up to set email alerts
|

C‐reactive protein (CRP) rs3093059C predicts poor mizolastine response in chronic spontaneous urticaria patients with elevated serum CRP level

Abstract: Chronic spontaneous urticaria (CSU) is a frequent disorder with recurrent itchy wheals and/or angioedema, and nearly 35% patients respond poorly to non‐sedating H1 antihistamine treatment. CRP gene encodes the C‐reactive protein, which is involved in the pathogenesis of CSU. To investigate the impacts of CRP polymorphisms on the susceptibility and therapeutic efficacy in the South Han CSU patients, we enrolled 145 CSU patients in our study. After 4‐week non‐sedating H1 antihistamine monotherapy treatment, more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Of note, a study by Yan et al revealed that the single nucleotide polymorphism rs216008 mutation may negatively affect the response to the sgAH desloratadine 26 . Additionally, certain CRP single nucleotide polymorphisms, such as those carrying the rs3093059C allele, may be linked to elevated serum CRP levels and a poor response to the sgAH mizolastine 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a study by Yan et al revealed that the single nucleotide polymorphism rs216008 mutation may negatively affect the response to the sgAH desloratadine 26 . Additionally, certain CRP single nucleotide polymorphisms, such as those carrying the rs3093059C allele, may be linked to elevated serum CRP levels and a poor response to the sgAH mizolastine 27 …”
Section: Discussionmentioning
confidence: 99%
“…26 Additionally, certain CRP single nucleotide polymorphisms, such as those carrying the rs3093059C allele, may be linked to elevated serum CRP levels and a poor response to the sgAH mizolastine. 27 CIndU, for example symptomatic dermographism and delayed pressure urticaria, may coexist with CSU, and its presence appears to indicate a longer duration of CSU and nonresponse to sgAHs. Indeed, CIndU is a common comorbidity of sgAH-refractory CSU, occurring in 24% of CSU patients.…”
Section: Potential Biomarkers Of Nonresponse or Poor Response To Seco...mentioning
confidence: 97%
“…CRP is a marker of acute inflammation, and TNF-α and IL-6 can stimulate liver cells to secrete CRP. In CU, serum IL-6 and CRP are positively correlated with disease severity and itching [96]. In addition, studies have found that CRP, D-dimer, and MMP-9 are related, indicating that inflammation and the coagulation system are relevant [43].…”
Section: C-reactive Proteinmentioning
confidence: 99%
“…It can predict the occurrence of AICU and prevent it [118]. CRP encodes CRP, and a recent study found that CRP rs3093059C predicts a poor mizolastine effect [119]. A research reported that C5AR1 −1,330T/G polymorphism predicts a poor desloratadine effect [120].…”
Section: Single-nucleotide Polymorphismmentioning
confidence: 99%
“…First, compared with the EQ-5D, the SF-6D has an additional dimension of vitality. Fatigue lack of sleep or insomnia are commonly reported in patients with CSU due to its constant itch accompanied by the collapse of urticarial (37)(38)(39), which has considerable influence on the dynamic of vitality. Second, the two instruments have different foci.…”
Section: Discussionmentioning
confidence: 99%